2006
DOI: 10.1590/s0101-81082006000100005
|View full text |Cite
|
Sign up to set email alerts
|

Contribuição dos domínios físico, social, psicológico e ambiental para a qualidade de vida global de idosos

Abstract: Este estudo investigou a contribuição de cada domínio da qualidade de vida (físico, social, psicológico e ambiental) na qualidade de vida global e em que extensão esses domínios explicam a qualidade de vida global de idosos residentes no município de Teixeiras, na Região Sudeste do Brasil. Trata-se de um estudo observacional de corte transversal, sendo a amostragem aleatória estratificada por sexo, uso do Programa Saúde da Família e microárea de saúde (n = 211, indivíduos com idade igual ou superior a 60 anos)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
54
9
144

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(218 citation statements)
references
References 28 publications
11
54
9
144
Order By: Relevance
“…In our study as well as in others (11,17), there was a predominance of females both in the control and the intervention group. This fact can be confirmed in accordance with the studies of (18,19), which found that in Brazil there is a higher prevalence of elderly women and that this difference increases within the aging process.…”
Section: Discussionsupporting
confidence: 87%
“…In our study as well as in others (11,17), there was a predominance of females both in the control and the intervention group. This fact can be confirmed in accordance with the studies of (18,19), which found that in Brazil there is a higher prevalence of elderly women and that this difference increases within the aging process.…”
Section: Discussionsupporting
confidence: 87%
“…In addition to the subjective aspects (perception), studies highlight objective predictors that influence SWB, among them, perceived health [3][4][5] . It is believed that this influence does not derive only from what elderly people feel physically, but from their perception of health or perceived health (PH).…”
Section: Introductionmentioning
confidence: 99%
“…The financial status of the elderly interferes directly in their daily life and thus in their perception of quality of life: better socioeconomic status is associated with better quality of life in the elderly, as observed in a study of elders in pain 44 . However, this association is not always seen 47 . Still, given the strong and wellknown association between these variables, the authors reported that lack of association may have been due to the geopolitical characteristics of the city where the data were collected (a predominantly rural setting with low cost of living and satisfactory health services).…”
Section: Discussionmentioning
confidence: 97%